Integrating SIGAP BPBD into Geospatial-Based Disaster Literacy Education in Garut Regency Schools - Amar Amrullah; Silmi Maulani Rohman; Rifal Pra Mesti Riswandi (Bulletin of Pedagogical Research, 2025)
This study explores the application of geospatial data in disaster management within Garut Regency through the Geospatial Information System (SIGAP) developed by the Regional Disaster Management Agency (BPBD). SIGAP integrates diverse datasets, including Digital Elevation Models, drone imagery, and satellite imagery, to support risk mapping and emergency decision-making. Employing a qualitative approach through interviews and documentation, this research highlights not only the system’s role in disaster mitigation but also its potential as an educational tool for fostering disaster awareness in schools. By providing spatial data as contextual learning materials, SIGAP enables geospatial-based disaster literacy, where teachers and students can engage with interactive digital maps and location-based data. The findings suggest that incorporating SIGAP into education enhances early disaster preparedness and promotes disaster literacy that is both data-driven and technology-oriented. This study contributes by (1) demonstrating the practical integration of geospatial data into local disaster management, (2) revealing the dual function of SIGAP as both a mitigation tool and an educational platform, and (3) offering a model for embedding geospatial-based disaster literacy into formal education to strengthen community resilience.